1996
DOI: 10.1017/s0950268800001540
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hantavirus in wild rodents in Northern Ireland

Abstract: A survey of evidence of rodent hantavirus infection in County Down, Northern Ireland was carried out by using immunofluorescence to detect virus antigen and antibody. Antibodies to hantavirus (R22 strain of Seoul virus and Hantaan 76-118) were found in 11/51 (21.6%) brown rats (Rattus norvegicus), 1/31 (3.2%) field mice (Apodemus sylvaticus) and 17/59 (28.8%) house mice (Mus domesticus). Seven rodents had evidence of hantavirus antigen in lung tissues. Antibody positive animals were significantly more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Recently, it was found that the HFRS emerged in Bayannaoer district of Inner Mongolia might be caused by SEOV imported from the neighboring HFRS endemic areas [Zhang et al, 2009b]. Up to date, SEOVs have been found worldwide [McCaughey et al, 1996;Heyman et al, 2004Heyman et al, , 2008Easterbrook et al, 2007;Cueto et al, 2008;Weissenbacher et al, 1996;Wang et al, 2000;Reynes et al, 2003;Shi et al, 2003;Plyusnina et al, 2004]. All these studies suggested that SEOVs could spread widely and even worldwide following travel of their hosts Rattus species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was found that the HFRS emerged in Bayannaoer district of Inner Mongolia might be caused by SEOV imported from the neighboring HFRS endemic areas [Zhang et al, 2009b]. Up to date, SEOVs have been found worldwide [McCaughey et al, 1996;Heyman et al, 2004Heyman et al, , 2008Easterbrook et al, 2007;Cueto et al, 2008;Weissenbacher et al, 1996;Wang et al, 2000;Reynes et al, 2003;Shi et al, 2003;Plyusnina et al, 2004]. All these studies suggested that SEOVs could spread widely and even worldwide following travel of their hosts Rattus species.…”
Section: Discussionmentioning
confidence: 99%
“…Hantaviruses show high genetic diversity as well as geographical clustering pattern of genetic variants within individual hantavirus type, such as HTNV [Zou et al, 2008a] and PUUV [Sironen et al, 2001]. In contrast, SEOV has been identified worldwide [McCaughey et al, 1996;Weissenbacher et al, 1996;Wang et al, 2000;Heyman et al, 2004Heyman et al, , 2009Plyusnina et al, 2004;Easterbrook et al, 2007;Cueto et al, 2008]. Notably, most of known SEOV variants including the majority of Chinese strains and also those from Brazil, Cambodia Egypt, France, Indonesia, Japan, North America, South Korea, and United Kingdom are genetically homogeneous [Wang et al, 2000;Reynes et al, 2003;Shi et al, 2003;Plyusnina et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…However, infection has been cleared from an infected laboratory colony of rats by use of caesarian section and seronegative fostering [61]. Seropositivity in juvenile animals is much less common than in adults and the highest antibody prevalence is generally in the oldest animals [62,63]. Bites and ®ghting have been implicated in transmission between adult rats [63,64].…”
Section: Infection In Rodentsmentioning
confidence: 99%
“…There are only three rodent species in Northern Ireland, Mus domesticus (house mouse), Apodemus sylvaticus (wood mouse) and R. norvegicus (brown rat) [153]. A survey of serological evidence of rodent hantavirus in Northern Ireland demonstrated antibodies to hantavirus in 11 (21.6%) of 51 R. norvegicus, 1 (3.2%) of 31 Apodemus sylvaticus and 17 (28.8%) of 59 M. domesticus [62].…”
Section: Hantaviruses In Northern Irelandmentioning
confidence: 99%
“…Early studies preceding the advent of serological techniques concentrated on laboratory mouse populations (Poiley 1970, Skinner & Knight 1971, Carthew & Verstraete 1978, Suzuki et al 1982. Following the wide adoption of serological techniques, the serological prevalence of selected viruses has been published for a very limited number of wild or laboratory-strain M. domesticus populations around the world (Van Vuuren et al 1990, Morita et al 1991b, McCaughey et al 1996. To date there has been no serological survey of viruses in wild house mice in the UK, although data have been reported for other rodent species endemic or introduced to the UK (Table 1).…”
mentioning
confidence: 99%